2022
DOI: 10.3390/ijerph19052586
|View full text |Cite
|
Sign up to set email alerts
|

The Fertility of a Concept: A Bibliometric Review of Human Flourishing

Abstract: Human flourishing is a thriving concept, whose use has greatly increased among academic researchers from a variety of fields, from the arts and humanities and psychology to the social and environmental sciences and economics. To better understand the concept’s success, this work proposes a bibliometric review, in which statistical methods and data mining were used to analyze 1829 documents, chosen from the Scopus database by searching the term “human flourishing”. Through cluster and network analyses, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…Previous studies on the academic use of HF have shown that the most relevant academic subject areas addressing the concept turned out to be Social Sciences, Arts and Humanities, Medicine, Psychology, Business, and Environmental Sciences 32 , which largely coincides with the relevance of the topics found in the current Twitter analysis: people and community; love and beauty; health, mental health, and well-being; and work, success, or employment. In addition, in both cases, there are some themes that cross-connect all these topics.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previous studies on the academic use of HF have shown that the most relevant academic subject areas addressing the concept turned out to be Social Sciences, Arts and Humanities, Medicine, Psychology, Business, and Environmental Sciences 32 , which largely coincides with the relevance of the topics found in the current Twitter analysis: people and community; love and beauty; health, mental health, and well-being; and work, success, or employment. In addition, in both cases, there are some themes that cross-connect all these topics.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, in both cases, there are some themes that cross-connect all these topics. In the case of academic production, it is the philosophical approach through keywords such as eudaimonia or virtue 32 ; while, in social media, the feeling that users have every day and the empathetic and generous mood they share can be translated as a popular idea of virtue and eudaimonia, which moves from valuing oneself to valuing others encouraging them to act in the world.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of the era of big data, scientific innovation based on scientific data mining has become an important tool. Through quantitative analysis of a large number of papers in a certain field, bibliometric analysis estimates the contribution of that field, reveals research hotspots, and predicts the future direction of the selected research field (Cebral-Loureda et al, 2022 ; Lin et al, 2022 ). A scientometric analysis of the papers is mainly performed using CiteSpace (Chaomei Chen, Drexel University, Philadelphia, PA, USA) and VOSviewer (Center for Science and Technology Studies, Leiden University, Leiden, Netherlands).…”
Section: Introductionmentioning
confidence: 99%
“…The bibliometric method is used to quantitatively analyse the research literature through database structure calculation and statistics [19]. This analysis can assess the research performance of groups and individuals [20] and identify academic characteristics of exchange and cooperation [21]. Therefore, bibliometric analysis can provide insight into previous studies and thereby directions for future [22].…”
Section: Introductionmentioning
confidence: 99%